Nursing Students' Experiences of Communication with Psychiatric Clients - M Ahmadifaraz; R Amini (Iran University of Medical Sciences, 2014)
Abstract   Background & Aim: Communicating with a psychiatric client due to the impairment in their cognitive, emotional and behavioral processes needs essential skills. Regarding the importance of acquiring knowledge of real experiences of nursing students in practice setting and improving the quality of education and considering the capabilities of qualitative approaches, this study was done with the aim of the recognition of nursing students' experiences of communication with psychiatric clients.   Material & Methods: It was a qualitative phenomenological study. Fifteen female nursing students of Islamic Azad University were recruited by purposeful sampling. Data was collected by in-depth unstructured interviews until saturation and analyzed using Colaizzi method.   Result: Ninety codes were emerged from the interview manuscripts that were classified into four major themes including: learning communication skills, task-based communication, Psycho-social adaptation, and Anxiety. Conclusion: Knowledge of students' lived experiences helps to better recognition of their communicative problems with psychiatric clients.